A Review of 3,4-methylenedioxymethamphetamine (MDMA)-Assisted Psychotherapy - Sessa, Ben; Higbed, Laurie; Nutt, David (Frontiers in Psychiatry, 2019)
This paper provides a brief review of the history, proposed pharmacological mechanisms, safety issues and clinical applications of the medicine 3,4-methylenedioxymethamphetamine (MDMA). Most clinical MDMA research in patients to date has focused on MDMA-assisted psychotherapy to treat posttraumatic stress disorder (PTSD). In this review paper other potential therapeutic applications for MDMA therapy are described, including contemporary studies treating anxiety associated with autism and the authors’ ongoing study exploring the potential role for MDMA-assisted psychotherapy to treat alcohol use disorder. MDMA therapy for PTSD is now entering the final Phase 3 stage of drug development, with a target set for licensing by the FDA and EMA in 2021. This means that if clinical efficacy criteria are achieved, MDMA would become a medicine.